Teacher Character across Levels of Study: Application of the 5 M Concept / Watak Pendidik Merentas Tahap Pengajian: Aplikasi konsep 5 M (Sains Humanika, 2021)
Islamic Education Teachers have a great responsibility and role in ensuring that the Islamic Education Philosophy and the National Education Philosophy are achieved. As a catalyst for both philosophies, the educational process that should be pursued is the process of ta'dib which is the process of cultivating manners. Through the era of globalization without borders and the ever-increasing turmoil of science, society is exposed to the collapse of manners. As such, the role of GPI is increasingly challenging. Therefore, this study aims to propose a GPI character that is relevant to the study based on the recommendation of the Ta'dib Al-Attas Model and the 5 MIM Teaching Model Ab. Halim Tamuri et al. The findings of this study show that there is a focus on GPI's character based on the level of education by always putting the vision of Muaddib as the foremost. This study has implications for Islamic Education Teachers and GPI educators.
Keywords: Watak Guru Pendidikan Islam; Model 5 MIM; Konsep Ta'dib